Peru case study: national Peruvian strategy against the spread of the coronavirus pandemic (COVID-19) - Alvarado, Karina (2020)
The present investigation is the study of the Peru case on the strategies implemented by the Peruvian government from the detection of patient zero with the objective of containing the spread of the pandemic decreed by the WHO for the coronavirus COVID-19. The behavior of the evolution of the number of infected from March 6 to April 24, 2020 is detailed. The first groups of measures were adopted from the detection of patient zero until the declaration by the WHO (World Health Organization) as a pandemic, accompanied by the implementation of protocols coupled to our health system and measures taken by the Peruvian government through Supreme Decree 008-2020-SA declaring a national health emergency for a period of 90 days. Subsequently, a series of measures evaluated were taken from March 12 to 26 and from March 27 to April 24, 2020, the date this study ends, detailing the strategies considered by the Peruvian government against the spread of the coronavirus COVID -19. Among the main actions taken by the Peruvian government before COVID-19 we have: (1) restrictions on the mobilization of people; (2) suspension of public and private meetings and events; (3) closure of borders at the international level and the transfer of people to different departments in Peruvian territory; (4) suspension of classes in educational institutions (Basic education, productive technical education center and universities), and (5) facilities and economic assistance incentives.